People and Institutions in the Roman Empire : Essays in Memory of Garrett G. Fagan - Gatzke, Andrea F.,; Brice, Lee L.,; Trundle, Matthew, (Mnemosyne, Supplements ;, 2020)
In People and Institutions in the Roman Empire colleagues honor Garrett Fagan for his contributions to our understanding and appreciation of Roman history and culture. In addition to reviewing and contextualizing Fagan's works and legacy, contributing authors pursue in their chapters topics and methodologies that interested Fagan - the experiences of individuals within Roman state and social institutions from the end of the Republic through the Empire and into Late Antiquity. Part One contextualizes Fagan's scholarship, demonstrating the diversity of his interests and his impact. Part Two considers the intersection between people and core state institutions: army, law, and religion. Part Three examines Roman social and cultural institutions such as the baths, arena, historiography, and provincial elite society.